Rare Suprasellar Chordoid Meningioma with INI1 Gene Mutation - Imad Fadl-Elmula; Rania Giha; Sawsan AH Deaf; Lamyaa Ahmed El Hassan; Ahmed M. Hassan; Mohamed AR Arbab (Sudan Journal of Medical Sciences)
Background: Chordoid Meningioma is a rare brain tumour characterized genetically by loss of genetic material from chromosome 22q at cytogenetic level resulting in mutation of NF2 gene.